2020
DOI: 10.1021/acs.jpcb.0c03768
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Self-Cleavage Reaction Mechanism of Hairpin Ribozyme

Abstract: Hairpin ribozyme catalyzes the reversible self-cleavage of phosphodiester bonds which plays prominent roles in key biological processes involving RNAs. Despite impressive advances on ribozymatic self-cleavage, critical aspects of its molecular reaction mechanism remain controversially debated. Here, we generate and analyze the multidimensional free energy landscape that underlies the reaction using extensive QM/MM metadynamics simulations to investigate in detail the full selfcleavage mechanism. This allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 94 publications
1
28
0
Order By: Relevance
“…networks can be expected for this transfer. There has been considerable importance given for studying water networkassisted proton exchange in enzyme catalysis, 24,30,[79][80][81][82][83] which is inter-linked with intrinsic pK a for the side chain of the concerned residues. For example, the Grotthuss mechanism 84 of proton transfer (propagation via H 3 O + ) happens when the side chain of the terminal residues are acidic (pK a { 7) whereas proton-hole like (OH À ) propagation 85 ensues when the side chain residues are basic (pK a c 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…networks can be expected for this transfer. There has been considerable importance given for studying water networkassisted proton exchange in enzyme catalysis, 24,30,[79][80][81][82][83] which is inter-linked with intrinsic pK a for the side chain of the concerned residues. For example, the Grotthuss mechanism 84 of proton transfer (propagation via H 3 O + ) happens when the side chain of the terminal residues are acidic (pK a { 7) whereas proton-hole like (OH À ) propagation 85 ensues when the side chain residues are basic (pK a c 7).…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] For example, the self-cleavage mechanism in hairpin ribosomes proceeds via proton transfer involving internal nucleophiles. 30 Moreover, Neves et al 19 reported nucleophilic disulfide bond rupture by the proton transfer mechanism in Protein Disulfide Isomerase (PDI), the mammalian counterpart of nDsbD. A similar reaction leading to the disulfide bond formation in nDsbD Red was suggested by Goulding and co-workers, 31 but the reaction mechanism remains undeciphered to date.…”
Section: Introductionmentioning
confidence: 93%
“…This profile has been computed from the minimum free energy pathway by using the corresponding three-dimensional free energy surface sampled at 10 kbar. Obviously, the chemical reaction at multi-kilobar pressure follows a strikingly different, yet much simpler pathway from what is known at 1 bar conditions. At such high pressures, the reaction occurs via a single-step concerted (A N D N ) mechanism, in stark contrast to the multistep associative (A N + D N ) mechanism at atmospheric pressure.…”
mentioning
confidence: 90%
“…In what follows, we report the effects of multi-kilobar pressures exclusively on the covalent chemical reaction which underlies the self-cleavage process of HpRz. Building upon our previous work on this chemical reaction exclusively at ambient conditions and on our detailed investigations of rather global conformational and local solvation processes at ambient and also high pressures ,, (as summarized in Supporting Information section 5) together with pertinent computational studies of ribozymes, we map the multidimensional free energy landscape of the chemical steps in HpRz self-cleavage using extensive ab initio QM/MM metadynamics simulations at high pressure conditions. Direct comparison to the reference scenario found at ambient conditions provides striking differences with considerable impact on the adaptability of HpRz to multi-kilobar pressure conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation